Pemeriksaan dan Edukasi Kesehatan Gigi dan Mulut bagi Siswa SMAN 2 Sidrap - Rezki Dirman; Asnuddin Asnuddin; Sri Sakinah; Utari Zulkaidah; Yulistina Yulistina (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Dental and oral health is one of the important things in maintaining a balance of body functions. The perception and behavior of the Indonesian people towards dental and oral health is still poor. The purpose of this community service is to improve dental and oral health through dental and oral health examinations and education for SMAN 2 Sidrap students. The method of implementing activities includes activity licensing, coordination with schools, preparation of counseling media, dental and oral health education and dental examination screening. Based on the results of the activities carried out by the team, it can be concluded that counseling (Dental Health Education) and dental health checks can be carried out properly and smoothly, get a positive response from students and there is good cooperation between teachers, schools and students. Educational activities for school students are carried out to improve dental and oral health and are proven to be able to improve their knowledge so that they can become pioneers for their families.